Research on Virtual Machine Placement in Cloud Data Center - Yongbing Fan; Tian Chen; Nan Chen; Zhilan Huang; Cui'e Lv (Dianxin kexue)
The key issues of virtual machine placement and the related algorithms, optimization goals, algorithms evaluation, benchmark models, verification tools were summarized. The typical algorithms of virtual machine placement were introduced. The characteristics of virtual machine placement of the backbone internet and the related reference values to the engineering practice of the cloud datacenter were analyzed. From the perspective of the adaptation of algorithm and engineering, several important principles for the key problems of the design and operation of cloud datacenter were proposed systematically, such as monitoring and measurement, service model, SLA and tariff design, cloud resource pool design, size and architecture of resource pool, service zone, migration control design, resource balance of resource pool, function design of logical network and physical network, and possible innovation.